Turn Characteristics of a Top World Class Athlete in Giant Slalom: A Case Study Assessing Current Performance Prediction Concepts - Spörri, J.; Kröll, J.; Schwameder, H.; Müller, E. (International Journal of Sports Science and Coaching, 2012)
Recently, four concepts explaining time differences in alpine ski racing have been suggested. Since the demands on a "well performed" turn are contradicting among these concepts, it is unclear which turn characteristics a skier should aim for in a specific giant slalom situation. During a video-based 3D-kinematic field measurement, single repetitive runs of a world class athlete were compared regarding section times over one turn and variables explaining time differences. None of the existing concepts was able to entirely explain time differences between different performed turns. However, it was found that the skier's line and timing played an important role for time over short sections. Hence, for both science and coaching, there is a need for more comprehensive approaches that include all variables influencing performance in one concept. In coaching, one such approach could be the training of implicit adaptation mechanisms in terms of situation-dependent line and/or timing strategies.